INNOVATIVE APPROACHES TO ERGONOMIC DESIGN IN MODERN ARCHITECTURE - Mustafayeva , Madina (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
The importance of psychological knowledge in the activities of a medical worker. Individual mental characteristics, qualities, processes, qualities, traits, behavior, actions, communication, consciousness, activity of the individual. A group of people and their influence